Assessing nutritional knowledge, attitudes and practices and body mass index of adolescent residents of orphanage institutions in Selangor and Malacca - bin Shaziman S.; Rani M.D.M.; Sulaiman W.N.W.; Abdullah M.Y.; Khairun Nain Nor Aripin; Nazefah Abdul Hamid; Zairina A. Rahman (Asian Network for Scientific Information, 2024)
Indexed by Scopus